HEAVY CLIMATE OF MILITARY VEHICLE TECHNOLOGIES PREPARING TO WORK IN CONDITIONS - Sunnatov Ixtiyor Xikmatovich (Scholars Digest Publishing, 2023)
The Republic of Uzbekistan is located in the heart of Asian countries, where the exploitation of military vehicles is carried out under different conditions. Flat roads with high-quality road cover, which remain unchanged throughout the year, and in mountainous and stepped areas, there are ways in which the climate is warmer in summer and much colder in winter, with dramatic changes in temperature. The reliable and safe operation of military vehicles depends in many ways on the quality of transportation in working in certain climatic conditions. The article outlines such problematic issues.
Keywords: automobile, technology, operation, road cover, military car, safe operation, transportation.